BENIGN PROSTATIC HYPERPLASIA - Gading, Citra; Kusuma Duarsa, Gede Wirya (Bali Journal of Medical and Health Sciences; vol 1no2 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Benign Prostatic Hyperplasia (BPH) is a nonmalignant enlargement of the prostate gland. BPH is commonly found in elderly man. The clinical manifestation include Lower Urinary Tract Syndrome (LUTS), Bladder Outlet Obstruction (BOO), acute and chronic urinary retention, urosepsis, urinary tract infection, bladder stone, and hematuria. BPH is diagnosed based on history taking, physical examintaion, rectal examination, laboratory examination, and urinary flow rate. Management of BPH based on patient symptom, include watchful waiting, medical therapy, minimally invasive therapy, and surgical therapy. Key words : Benign Prostatic Hyperplasia (BPH), Lower Urinary Tract Syndrome (LUTS), Prostate, Urethra Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}